1972
DOI: 10.1111/j.1528-1157.1972.tb04580.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Cerebellum in Cat Penicillin Epilepsy

Abstract: SUMMARY Discrete, gross, and deep cerebellar stimulation tended to inhibit a cortical penicillin‐induced focal epilepsy in the cat. The cerebellar cortical areas which, when stimulated electrically, most frequently expressed inhibition were the right paramedian lobes and the pyramis. When these same areas were ablated, focal seizures were facilitated. The data support the beliefs of previous workers that the cerebellum may play an active role in seizure suppression. Résumé La stimulation cérébelleuse légère, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
4

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 12 publications
3
28
0
4
Order By: Relevance
“…Numerous animal studies have demonstrated that electrical stimulation of the cerebellum may abort electrically or chemically induced seizures and drastically alter the electrophysiological profile of the neuronal tissue in vitro and in vivo. 1,2,5,8,[13][14][15]19,21,22,26,28,30,35,38,39,41,42,48,49,52,53 However, there are several issues that remain to be resolved and important questions that need to be answered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous animal studies have demonstrated that electrical stimulation of the cerebellum may abort electrically or chemically induced seizures and drastically alter the electrophysiological profile of the neuronal tissue in vitro and in vivo. 1,2,5,8,[13][14][15]19,21,22,26,28,30,35,38,39,41,42,48,49,52,53 However, there are several issues that remain to be resolved and important questions that need to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…They drew the conclusions that vermian and superomedial cortical stimulation appeared to be more efficient than lateral cortical stimulation, and that CS seemed more effective in models of generalized or focal epilepsy of the limbic system than those of focal epilepsy of the sensorimotor cerebral cortex. In our current review, it appears that CS of deep structures has been used in only 3 animal experimental studies, and in 2 of these there was inhibition of seizure activity, 1,28 whereas in the other study there was no effect. 26 Interestingly, stimulation of the dentate nucleus showed seizure inhibition in one study, 28 no effect on seizure activity in another, 26 and prolongation of seizure duration in the third.…”
Section: Animal Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The EEG findings later were confirmed by Cooke and Snider (1953). Several subsequent animal studies showed favorable effects of surface or deep cerebellar stimulation on inhibiting seizures in animal models (Dow et al, 1962;Hutton et al, 1972;Babb et al, 1974;Strain et al, 1978). Stimulation of the paramedian lobule at 300 Hz (Cooke and Snider, 1955;Iwata and Snider, 1959), and also the fastigial deep nucleus, inhibited electrically induced seizures in cortex and hippocampus.…”
Section: Cerebellar Stimulation For Epilepsymentioning
confidence: 81%
“…Moruzzi und Magoun fanden eine Verminderung der Dezerebrationsstarre bei Ratten durch Hochfrequenzstimulation des Kleinhirns [76]. Daraufhin wurden in verschiedenen Institutionen Tierversuche zur Anfallskontrolle durch Kleinhirnstimulation durchgeführt, die sowohl positive [5,42,51] als auch negative [47,62,79] Ergebnisse brachten. Cooper et alversuchten schließ-lich 1970, menschliche Anfälle mit Kleinhirnstimulation zu behandeln und berichteten über Anfallsfreiheit bei 27% der Probanden in unkontrollierten Fallserien [27,28,29].Diese Resultate konnten jedoch in doppelblind kontrollierten Studien [110,127] nicht bestätigt werden.…”
unclassified